On the real effects of bank bailouts: Micro-evidence from Japan - Mariassunta Giannetti; Andrei Simonov (Fondazione Eni Enrico Mattei (FEEM), 2009)
Exploiting the Japanese banking crisis as a laboratory, we provide firm-level evidence on the real effects of bank bailouts. Government recapitalizations result in positive abnormal returns for the clients of recapitalized banks. After recapitalizations, banks extend larger loans to their clients and some firms increase investment, but do not create more jobs than comparable firms. Most importantly, recapitalizations allow banks to extend larger loans to low and high quality firms alike, and low quality firms experience higher abnormal returns than other firms. Interestingly, recapitalizations by private investors have similar effects. Moreover, bank mergers engineered to enhance bank stability appear to hurt the borrowers of the sounder banks involved in the mergers.
Keywords: G21; G34; 330; Recapitalization; Merger; Banking Crisis